ISLAMIC JOURNALISM: ETHICAL CONSIDERATIONS AND CHALLENGES IN THE REPRESENTATION OF MUSLIM COMMUNITIES - Mujawaroh Annafi; Faisal Razak; Syafiq Amir (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Representation of Muslim communities within contemporary media environments continues to generate ethical concerns related to stereotyping, ideological framing, and imbalanced journalism practices. Mainstream media frequently associate Islam with conflict, extremism, and political instability, while limited attention is given to the diversity, social contributions, and cultural complexity of Muslim societies. Islamic journalism has therefore emerged as an important ethical communication framework emphasizing fairness, contextual accuracy, social responsibility, and respectful representation. This study aimed to examine the ethical considerations and practical challenges encountered in the representation of Muslim communities within contemporary journalism environments. Qualitative descriptive methodology combined with critical discourse analysis was employed through media content analysis, in-depth interviews, and document review involving mainstream journalists, Islamic media practitioners, and communication scholars. The findings revealed that institutional pressure, digital competition, political narratives, and algorithm-driven communication systems significantly influenced representational imbalance concerning Muslim communities. Islamic-oriented journalism platforms demonstrated stronger commitment to ethical reporting principles, including balanced representation, contextual explanation, and community-centered narratives. Ethical journalism practices were also found to contribute positively to intercultural understanding and reduction of harmful stereotypes. This study concludes that Islamic journalism represents an important ethical alternative capable of strengthening inclusive communication, promoting socially responsible reporting, and encouraging more balanced representation of Muslim communities within increasingly polarized global media environments.